Profile of reticulated platelets in the early, subacute and late phases after transient ischemic attack or ischemic stroke. (2nd January 2022) - Lim, ST; Tobin, WO; Murphy, SJX; Kinsella, JA; Smith, DR; Lim, SY; Murphy, SM; Coughlan, T; Collins, DR; O'Neill, D; Egan, B; Tierney, S; et al.
Abstract: Information regarding the profile of reticulated platelets (RP) in ischemic cerebrovascular disease (CVD) patients is limited. Data from two prospective, observational, case-control studies were combined to compare the %RP using whole blood flow cytometry in patients ≤ 4 weeks of TIA/stroke onset (baseline, N = 210), and 14 ±7 days (14d, N = 182) and ≥ 90 days (90d, N = 145) after starting or changing antiplatelet therapy with healthy controls (N = 34). There were no differences in median %RP between the overall CVD patient population at baseline or 14d vs . controls (P ≥ 0.2). However, the median %RP was significantly higher in CVD patients overall at 90d ( P = .036), and in the subgroup of patients with "lacunar" TIA/ischemic stroke at baseline ( P = .04) and at 90d ( P = .01), but not at 14d ( P = .06) vs . controls. There were no significant differences in the median %RP between other TIA/stroke subgroups and controls (P ≥ 0.05). Elevated circulating reticulated platelets, as a marker of increased platelet production/turnover, may occur following an ischemic event in a well-phenotyped TIA/ischemic stroke population overall, but may precede symptom onset at least in the subgroup with small vessel occlusion. These data improve our understanding of the profile of reticulated platelets in CVD patients.